Targeting MAO-B with Small-Molecule Inhibitors: A Decade of Advances in Anticancer Research (2012–2024) - Iyman Alsaad; Diana M. A. Abdel Rahman; Ola Al-Tamimi; Shayma’a A. Alhaj; Dima A. Sabbah; Rima Hajjo; Sanaa K. Bardaweel (Molecules)
Monoamine oxidase B (MAO-B) is a key enzyme in the mitochondrial outer membrane, pivotal for the oxidative deamination of biogenic amines. Its overexpression has been implicated in the pathogenesis of several cancers, including glioblastoma and colorectal, lung, renal, and bladder cancers, primarily through the increased production of reactive oxygen species (ROS). Inhibition of MAO-B impedes cell proliferation, making it a potential therapeutic target. Various monoamine oxidase B inhibitors have shown promise in inhibiting tumor growth and inducing apoptosis across different cancer types. In this review, we investigate MAO-B network biology, which highlighted glycolysis pathways as notable links between MAO-B and cancer. Further molecular modeling analysis illustrated the basis of MAO-B ligand binding, revealing a hydrophobic binding pocket, with key residues such as Tyr398 and Tyr435 playing crucial roles in substrate oxidation. MAO-B inhibitors that were reportsed in the literature (2012–2024) and their potential application in cancer therapy were discussed, highlighting key molecular scaffolds, such as propargyl analogs of phenyl alkyl amines, hydrazine derivatives, cyclopropylamine derivatives, MAO-B activated pro-drugs, and natural phenylpropanoid derivatives. The reported literature underscores the therapeutic potential of MAO-B inhibitors as versatile anticancer agents, warranting further investigation to optimize their efficacy and specificity across various malignancies.